PENGARUH BRAND IMAGE DAN POINT OF DIFFERENCE TERHADAP LOYALITAS KONSUMEN UBI YAKON - Muhammad Khaesar A; Novandra Fitriyadi; Dinda Tri Suci R; Arbita Ully Anggraeni; Ayu Nursari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the influence of Brand Image and Point of Difference on Consumer Loyalty toward yakon sweet potato products in Bandar Lampung City. The increasing competition in the functional food industry requires businesses to build a strong brand image and create distinctive product characteristics that differentiate them from competitors. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to consumers of yakon sweet potato products and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The results indicate that Brand Image has a significant effect on Consumer Loyalty, while Point of Difference does not have a significant effect on Consumer Loyalty.** These findings suggest that a positive brand image can enhance consumer trust and commitment to repurchase the product, whereas product differentiation has not become a primary factor in building consumer loyalty. Therefore, business owners should focus on strengthening their brand image as a strategy to increase consumer loyalty toward yakon sweet potato products.